UPAYA PENINGKATAN PENGETAHUAN DAN KEMAMPUAN PEMILIHAN OBAT PADA COASS (DOKTER MUDA) UNIVERSITAS JENDERAL ACHMAD YANI (UNJANI) CIMAHI DI RUMAH SAKIT DUSTIRA CIMAHI DENGAN METODE DISKUSI KELOMPOK KECIL (DKK) MENGGUNAKAN MODUL GUIDE TO GOOD PRESCRIBING (GGP) - , Neneng Sulistiani, dr. Sulanto S. Danu, SpFk ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Prescribing drugs is defined to be irrational if provide a small benefit or none at all, while the benefits are not worthed with side effects or cost. Based on interviews with internship medical student (CoAss) of Universitas Jenderal Achmad Yani in Dustira Hospital Cimahi about rational treatment, student still hesitate to chose the drugs selection, writing prescription and give drug information. To overcome this, the training effort can be reached by Guide to Good prescribing (GGP) module that have been developed and tested at the Faculty of Medicine in several university in the world with outcomes that can improve the drug selection skills using the SGD (Small Group Discussion) method. Objective: The aim of this study is to increase internship medical student (CoAss) of Universitas Jenderal Achmad Yani Cimahi in Dustira Hospital Cimahi knowledge and drug selection skills with SGD method using GGP module. Methods: This study is a quasi-experimental studies with the design of pre and post-test. Results: The results showed that the average score of knowledge and drug selection skilss on the respondents were significant difference with p <0.05. The mean score at pre-test was 27.3 which increased to 29.7 during post-test1 and increased to 32.3 at post-test2. The results showed that in terms of drug selection, after given intervention almost all the respondents could determine the choice of the right drug for each case which are given, but incomplete in terms of prescribing so that a maximum score not achieved (maximum score 60). Conclusion: There is increased knowledge and drug selection skills to internship medical student (CoAss) of Universitas Jenderal Achmad Yani in Dustira Hospital Cimahi before and after intervention with SGD method using GPP module. Intervention by SGD method using GGP module can effectively improve the knowlegde and drug selection skills, but still less effective in term of prescribing and giving informations to patients.